2003
DOI: 10.1002/adma.200304602
|View full text |Cite
|
Sign up to set email alerts
|

Functional Molecularly Imprinted Polymer Microstructures Fabricated Using Microstereolithography

Abstract: ExperimentalChemicals: Vanadyl sulfate pentahydrate (purum, Fluka), TEOS (98 %, Fluka), hydrogen peroxide (30 %, Perhydrol, p.a., Merck), ammonia (25 %, p.a., Merck), isopropanol (99.5 %, J. T. Baker) were used as purchased.Synthesis: Fibrous V 3 O 7´H2 O template crystals were prepared hydrothermally according to : an aqueous solution of VOSO 4 (0.15 M) was sealed in a poly(tetrafluoroethylene)-lined autoclave (Parr bomb 4749, 23 mL capacity) and heated at 180±220 C for 1±2 days. The resulting suspension was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 24 publications
0
47
0
2
Order By: Relevance
“…On the other hand, geometric structures including rough structures and regular micro/nano patterns are also crucial [13,14]. To obtain polymer regular micro/ nano geometric surfaces, various nanoprocessing approaches can be employed, including nanoporous template wetting [15], capillary lithography [16], nanoimprint lithography [17], microstereolithography [18], template rolling press [19], and water spreading of carbon nanotubes [20]. A number of theoretical and experimental studies indicated that polymer aligned nanopillar arrays or carbon nanotube arrays could exhibit hydrophobic or surperhydrophobic feature [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, geometric structures including rough structures and regular micro/nano patterns are also crucial [13,14]. To obtain polymer regular micro/ nano geometric surfaces, various nanoprocessing approaches can be employed, including nanoporous template wetting [15], capillary lithography [16], nanoimprint lithography [17], microstereolithography [18], template rolling press [19], and water spreading of carbon nanotubes [20]. A number of theoretical and experimental studies indicated that polymer aligned nanopillar arrays or carbon nanotube arrays could exhibit hydrophobic or surperhydrophobic feature [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, different methods for MIP micro/ nanostructuring have been demonstrated. For example, UV, 3 evanescent wave 4 and microstereo lithographic techniques 5 were used to synthesize MIP features with microscale lateral resolution. To achieve sub-micron lateral resolution, nanoimprint lithography was shown to be successful; 6 however, it requires a mould or stamp contacting the pre-polymerization mixture, which may contaminate the resulting MIP surface.…”
Section: Introductionmentioning
confidence: 99%
“…For high performance, development of new materials and novel fabrication techniques has been actively studied in this area. Synthesis of new materials for nanoimprinting lithography, soft lithography, microfluidic technique, and plastic electronics is of interest for chemists to expand the scope of current nanotechnology to advanced levels [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%